Polish 'Pawns' between nationalism and neoliberalism in British newspaper coverage of post-European Union enlargement polish immigration. (August 2016) - Hoops, Joshua F; Thomas, Ryan J; Drzewiecka, Jolanta A
The United Kingdom was one of four countries to open its labor market to Polish workers post-European Union enlargement in 2004. In this study, we analyze the articulation of discourses of neoliberalism and nationalism through examination of mediated representations of Polish immigrants in four British newspapers. We argue that within the coverage analyzed, across format and political orientation, neoliberal values were promoted and the seeming tension between the two ideologies was articulated in ways that could be discursively mobilized to further particular political, economic, and media objectives. Polish immigrants were constituted as discursive pawns employed by various political and media entities toward these contrasting agendas.